Sifat Fisikokimia Pati Tahan Cerna Hasil Hidrolisis Asam dan Heat Moisture Treatment pada Pati Maizena - Tuti Wukirsari; Endang Saepuddin; Ivanka Putri Hanafiah (Jurnal Agritechno, 2022)
The increasing of diabetes prevalence both in Indonesia and in the world requires innovations in the food sector. In this study, modification of corn starch was carried out by acid hydrolysis (HA) and heat moisture treatment (HMT) with various combinations of HCl concentration and duration of HMT. Then the effect of HA and/or HMT modification on the physicochemical properties of corn starch was determined. The results showed that HA and/or HMT treatment reduced digestibility up to 56%, swelling power up to 10 times, and viscosity up to 2 times in modified starch. These data prove the rearrangement of the modified corn starch granule to become denser and more crystalline.